Unobserved Actions of Mutual Funds - Kacperczyk, Marcin; Sialm, Clemens; Zheng, Lu (Review of Financial Studies, 2008)
Despite extensive disclosure requirements, mutual fund investors do not observe all actions of fund managers. We estimate the impact of unobserved actions on fund returns using the return gap—the difference between the reported fund return and the return on a portfolio that invests in the previously disclosed fund holdings. We document that unobserved actions of some funds persistently create value, while such actions of other funds destroy value. Our main result shows that the return gap predicts fund performance. (JEL G11, G23) Despite extensive disclosure requirements, mutual fund investors do not observe all actions of fund managers. For example, fund investors do not observe the exact timing of trades and the corresponding transaction costs. On the one hand, fund investors may benefit from unobserved interim trades by skilled fund managers who use their informational advantage to time the purchases and the sales of individual stocks optimally. On the other hand, they may bear hidden costs, such as trading costs, agency costs, and negative investor externalities. In this paper, we analyze the